Periodicity of Xylem Growth of Four Planted Tree Species from Malaysian Forest - Abdul Jalil, Nor Rahmat (1995)
Tree ring analysis is an important aspect in forestry and ecology as it provides information on factors influencing growth rates, wood production and quality, rotation times, and replacement rates before it will be felled and used. Growth rate information from tree ring analysis is useful for harvesting, plantation planning, sustenance of natural forest, as well as managing timber as a renewable resource. This study was carried out to detennine the periodicity of xylem growth in four selected Malaysian plantation tree species, viz., Hevea brasiliensis (rubberwood) 8-year old, Pinus caribaea (Pine) 10-year old, Shorea /eprosu/a (Meranti Tembaga) 22-year old and Dryoba/anops aromatica (Kapor) 21-year old, through cambium wounding by minute pinning and knife-cutting. Diameter growth increments were measured by a dendrometer band and the climatic data were also collected. After a year, one tree of each species was felled, and the cambial response to wounding measured. The xylem produced subsequent to the cambial response was measured in two different ways, i.e., total radial growth increment (length from the scars to the end of the cambium) and actual radial growth increment (length from the growth zone boundatyl standard line to the scars).